Do yoga and meditation moderate the relationship between negative life events and depressive symptoms? Analysis of a national cross-sectional survey of Australian women - Lauche, Romy; Anheyer, Dennis; Uebelacker, Lisa A.; Sibbritt, David; Adams, Jon; Cramer, Holger (Frontiers in Psychology, 2023)
This study aims to examine the role of yoga/meditation in the relationship between negative life events, stress and depression.The Australian Longitudinal Study on Women's Health (ALSWH) surveyed 7186 women aged 36-43 years (mean age 39.2 years; 57.2% university degree) in 2015. Mediation and moderation analyses were conducted to examine whether yoga/meditation practice moderated those relationships.Yoga/meditation was practised by 27.5% of participants, 33.2% reported negative life events in the past 12 months, and 24% had clinical depression. Perceived stress partially mediated the association between negative life events and depressive symptoms (B=6.28; 95%CI 5.65; 6.92). Social support (B=-0.38; 95%CI -0.54; -0.23) and optimism (B=-0.25;95%CI -0.31;-0.18) moderated the association between stress and depressive symptoms. Yoga/meditation practice moderated the direct association between negative life events and depressive symptoms (B=-0.92; 95%CI -1.67; -0.18).Yoga/meditation use was a significant moderator of the relationship between negative life events and depression. Yoga/mediation use did not act via reducing perceived stress, but instead was found to dampen the influence of negative life events on depression directly. More research on how yoga has an impact on depression is warranted.